Investigating the Learning Process of Folk Dances Using Mobile Augmented Reality - Iris Kico (Applied Sciences, 2020)
Learning how to dance is not an easy task and traditional teaching methods are the main approach. Digital technologies (such as video recordings of dances) have already been successfully used in combination with the traditional methods. However, there are other emerging technologies such as virtual and augmented reality that have the potential of providing greater assistance, in order to speed up the process as well as assisting the learners. This paper presents a prototype mobile augmented reality application for assisting the process of learning folk dances. Initially, a folk dance was digitized based on recordings from professional dancers. Avatar representations (of either male or female) are synchronized with the digital representation of the dance. To assess the effectiveness of mobile augmented reality, it was comparatively evaluated with a large back-projection system in laboratory conditions. Twenty healthy participants took part in the study, and their movements were captured using motion capture system and then compared with the recordings from the professional dancers. Experimental results indicate that augmented reality (AR) application has the potential to be used for learning process.